Implementasi Pengembangan Ekowisata Di Kabupaten Banyuwangi (Studi Kasus Obyek Wisata Kawah Ijen) - Yudharta, Putu Dharmanu (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
As a region that has enormous potential and opportunities in the tourism sector are diverse, Banyuwangi district will be able to develop into an added value in the future. One of the objects/tourist attraction (ODTW) that Ijen crater area, the selection Ijen crater is quite realistic for a tourism icon of Banyuwangi seen more than its natural potential to sell to tourists. The concept of ecotourism is the basis of tourism development in the crater of Ijen. Ecotourism policy in line with central government policy that seeks to preserve the nature in any conservation area in each region. Minister Regulation number 33 of 2009 on guidelines for the development of Ecotourism in the area, requiring the area under the constitution for the regional tourism planning guided by the ecotourism planning. The development of ecotourism is a revolutionary and visionary step, because the development of sustainable tourism which combines nature, culture and local community participation. Ecotourism aims to reduce the impact of tourism development on existing ecosystems such as forests, fauna and flora. And it involves the people around tourism in the process of tourism development that will be able to increase the income of the surrounding community. This is a concept initiated by the government of Banyuwangi Distric to developed as a tourism attraction majority are natural attractions that are vulnerable to damage if any management. This study was conducted to explore the dynamics of the implementation of the development of ecotourism as a form of sustainable economic development.